The Effectiveness of Using Augmented Reality (AR)-Based Learning Media to Enhance Arabic Speaking Skills in High School - Ash Shidiqiyah, Firstiyana Romadlon; Nurhidayati, Nurhidayati; Furqon, Muhammad Rizalul (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This study aims to analyze the effectiveness and implementation of Augmented Reality (AR)-based learning media in enhancing Arabic speaking skills at SMA Islam Al-Ma’arif Singosari. Arabic speaking skill learning often faces challenges such as a lack of interaction, minimal speaking practice, and low student motivation and confidence. Therefore, technology-based innovations like AR are needed to create a more interactive and contextual learning experience. This research employs a Pre-Experimental method with a One-Group Pre-Test and Post-Test design. The sample consists of 27 students from grade XI IPS 3, with research instruments including speaking tests, observations, and documentation. Data were analyzed using the Wilcoxon test and N-Gain test. The results show that AR-based media is effective in improving Arabic speaking skills. The average pre-test score of 55.7 increased to 86.2 in the post-test, with the Wilcoxon test yielding a significance value of 0.000 (p < 0.05), indicating a statistically significant improvement. The N-Gain score of 0.6650 (66.5%) falls into the moderate category. In terms of implementation, the observation results indicate that students responded positively to the use of AR media, showing increased engagement, enthusiasm, and willingness to practice speaking through interactive 3D visualizations and audio conversations. These findings suggest that AR media not only enhances students’ speaking performance but also supports an engaging and supportive learning environment.